2015
DOI: 10.1590/0102-33062015abb0060
|View full text |Cite
|
Sign up to set email alerts
|

Alpha and beta diversity of phytoplankton in two subtropical eutrophic streams in southern Brazil

Abstract: This paper reports the alpha and beta diversity of phytoplankton communities of two streams differing in land use. We analyzed which environmental conditions affect diversity of the phytoplankton communities and tested the hypothesis that stream stretches protected by forests will have lower species richness, whereas higher beta-diversity would occur among the non-protected stretches. Samples were taken quarterly, from February to November 2012, in nine stretches, including four non-protected stretches, two pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…e density classes were accepted following [30], satellite species (D < 1%); subdominant species (1 < D < 5%); dominant species (D > 5%). All types of microbiota, that is, phytoplankton, bacterioplankton planktonic protists, and zooplankton occurrence frequencies were categorized as constant for species found in >50% of the habitats; common when found between 25% and 50% of the habitats; and accidental or rare species when found in <25% of the habitats [31].…”
Section: Discussionmentioning
confidence: 99%
“…e density classes were accepted following [30], satellite species (D < 1%); subdominant species (1 < D < 5%); dominant species (D > 5%). All types of microbiota, that is, phytoplankton, bacterioplankton planktonic protists, and zooplankton occurrence frequencies were categorized as constant for species found in >50% of the habitats; common when found between 25% and 50% of the habitats; and accidental or rare species when found in <25% of the habitats [31].…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, βW in the facultative pond was high in September (20.7) and low in October (12), whereas it was high in April (20.2) and lower in October (8.6) in the maturation pond. Both ponds had relatively low βW, indicating a low turnover in the phytoplankton community, i.e., ponds have high similarity (Schuster et al, 2015) and environments with high productivity can present low βw (Zorzal-Almeida et al, 2017). The maturation pond had higher βW in the rainy season, whereas it was higher in the dry season in the facultative pond.…”
Section: Phytoplankton Community Structurementioning
confidence: 97%
“…Schuster et al (2015) found it in a first-order stream with a small strip of riparian vegetation and adjacent areas with corn crop in Santa Catatina State. Here we describe and illustrate a new Cymbella species found in first-and second-order oligotrophic streams from Rio Grande do Sul State (Brazil) in areas that have not previously been the subject of diatom studies.…”
Section: Introductionmentioning
confidence: 96%
“…The Cymbella aspera group is rarely recorded to Brazil; only Metzeltin and Lange-Bertalot (1998) and Schuster et al (2015) have cited it. Schuster et al (2015) found it in a first-order stream with a small strip of riparian vegetation and adjacent areas with corn crop in Santa Catatina State.…”
Section: Introductionmentioning
confidence: 99%